Quality Test of Peanut Sauce Made from Different Ratio of Hyacinth Beans (Lablab purpureus (L.) Sweet) and Groundnut (Arachis hypogaea L.) - Budi Wibowotomo; Issutarti Issutarti; Jesi Kurnia Dewi Treeseff (Bulletin of Culinary Art and Hospitality, 2022)
This study aims to analyze the proximate content (protein, fat, water content, ash content, and carbohydrate), as well as the effect of hyacinth beans and groundnuts ratios on the organoleptic properties of peanut sauce. This study was an experimental study using a Completely Randomized Design (CRD). The results showed that the hyacinth beans and groundnuts ratio significantly affected the proximate test results, hedonic quality of texture, color, and panelist preferences on the color of peanut sauce. The highest protein content was found in the 50:50 hyacinth beans and groundnuts ratio with the lowest water and carbohydrate content. Meanwhile, the lowest fat and ash content were observed in the 90:10 ratio of hyacinth beans and groundnuts. The highest texture hedonic qualities were identified in peanut sauce with a 50 percent: 50 percent hyacinth and groundnuts ratio, compared to the crude category (3.61). Additionally, the highest hedonic color values were observed in the peanut sauce made from 50:50 and 70:30 ratios, with the values of 3.63 and 3.7, respectively. Meanwhile, in the category of slightly dark chocolate, the preferred level is the value of 4.19 and 4.21, respectively. The hedonic quality of taste and flavor ranges between 4.11-4.17 (delicious, tasty) and 4.51-4.66 (a bit not rotten-rotten). The preference level for texture, taste, and flavor showed no significant difference with the values of 4.24-4.31 (similar), 4.13-4.16 (similar), and 4.1-4, 39 (similar), respectively, on all samples.